Effects of Fiber Consumption in Lowering Cholesterol Level - Brigitta Olivia Sinulingga (Jurnal Penelitian Sains, 2020)
High cholesterol is one of the risk factor for non-communicable disease such as the formation of artherosclerosis and metabolic disease. The number of non-communicable disease continue to increase and becomes one of the health problems in the world including Indonesia. community eating habbit that changed for the worse with the times are one of the biggest reason why the number of deaths for non-communicable diseases continues to increase. there are efforts that can be made to prevent the condition of hypercholesterolemia, a state of disturbance of blood fat levels of more than 240 mg / dl is to modify the lifestyle with a high-fiber diet. There are so many health benefits that can be obtained from eating dietary fiber. In addition to lowering cholesterol, dietary fiber can also increase insulin sensitivity, stimulate reducing blood glucose diffusion, hormonal effects by decreasing insulin secretion, increasing fat oxidation, and reducing fat storage due to increased satiety. Therefore, the adequacy of food fiber intake in the daily diet is very important. According to Southgate daily fiber intake is 16-28 g / day. Whereas the Dietary Guidlenes of American recommend consuming foods containing fiber and starch in amounts of 20-35 g / day